Sosialisasi Literasi Keuangan ( Pengelolaan Uang & Sosialisasi Menabung ) Pada Siswa SDN 24 Kota Bengkulu Sebagai Upaya Pembentukan Karakter Mengelola Keuangan Sejak Dini - Daniarti, Rahma; Soleh, Ahmad; Fitriano, Yun; Abi, Yudi Irawan (Universitas Dehasen Bengkulu, 2024)
Financial literacy is an important lesson to teach from an early age. Introducing the value of money and the culture of saving to children can shape wise financial behavior in the future. This socialization discusses the importance of financial literacy for young children. The community service methods applied include problem identification, needs analysis, and implementation of outreach through material presentations, questions and answers, and discussions. The material presented includes basic knowledge about money, the importance of saving, and spending money wisely. The results of the activity showed an increase in students' understanding of money management, the importance of saving, and the ability to distinguish between needs and wants. The aim of this service is to shape the character of children who are able to manage finances from an early age, which is expected to help them in their future adult lives. With this financial literacy outreach, students at SD N 24 Bengkulu City have become smarter and wiser in understanding how to manage their finances.